Telomerase activity in the vaginal margins of radical hysterectomy in patients with carcinoma of the cervix: correlation with histology and human papillomavirus. Issue 3 (1st April 2006) - Triginelli, S. A.; Silva-Filho, A. L.; Traiman, P.; Silva, F. M.U.; Chaves-Dias, M. C.G.; Oliveira, G. C.; Cunha-Melo, J. R.
Abstract : This study was undertaken to evaluate the telomerase activity both in the tumor and in the vaginal margins of radical hysterectomy in patients with squamous cell carcinoma (SCC) of the cervix. Thirty-three patients with SCC of the cervix (study group) and 13 patients with uterine myoma (control group) were prospectively studied. Tissue samples were taken from the tumor or cervix, anterior vaginal margin (AVM), and posterior vaginal margin (PVM). The specimens were analyzed by histopathology, by a telomerase PCR-TRAP-ELISA kit, and by polymerase chain reaction using human papillomavirus (HPV) DNA. The telomerase activity was significantly higher in the tumor than in the benign cervix ( P < 0.001). There was no difference in telomerase activity in the AVM and PVM in patients with cervical carcinoma compared to the control group. Telomerase activity was associated with the presence of histologic malignancy in the PVM of patients submitted to radical hysterectomy ( P = 0.03). This association was not observed with the presence of HPV in AVM or PVM in the study group. Telomerase activity is a marker of histologic malignancy in patients with SCC of the cervix. There was no association between the telomerase activity and the presence of HPV in vaginal margins of patients submitted to radical hysterectomy.